ANALISIS STRATEGI PENDIDIK DALAM MENGEMBANGKAN KARAKTER MANDIRI PADA PESERTA DIDIK MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SEKOLAH DASAR : Penelitian Kualitatif - Shanty, Shanty Okta Andelia; Dayu, Dayu Rika Perdana; Niken Yuni Astiti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problems found when implementing the Pancasila Student Profile Strengthening Project (P5) educators still have difficulty in determining the right strategy to develop independent character in students when implementing the Pancasila Student Profile Strengthening Project (P5). This study aimed to find out how the educator's strategy in developing independent character through the Pancasila Student Profile Strengthening Project (P5), especially at SD Negeri 01 Metro Utara. This research used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the research conducted show that the implementation of the Pancasila Student Profile Strengthening Project (P5) has been running in a structured manner and has a positive impact in shaping independent character in students. Educators at SD Negeri 1 Metro Utara act as companions and motivators who always guide students according to their individual needs. For specific strategies, educators have not implemented but the learning process was carried out gradually and varied so that students are active and do not feel bored during activities or learning so that they can foster an independent attitude in students.